Правове оформлення створення НКВС УСРР (1934 р.) - Окіпнюк, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The article is dedicated to the process of reorganization and legal implementation of NKVD in Soviet Ukraine as well as to the widening of extrajudicial authorities of punitive institutions.